Hard Bargaining - Bronfenbrenner, Kate (Labour / Le Travail, 2003)
Discusses employer tactics - notably the threat of plant closure - to prevent US workers from organizing. Concludes there will be a worldwide race to the bottom in the absence of the collective voice and power that unions bring.